2016
DOI: 10.15252/emmm.201606403
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐associated membrane collapse is a common pathomechanism in SIGMAR1‐ and SOD1‐linked ALS

Abstract: A homozygous mutation in the gene for sigma 1 receptor (Sig1R) is a cause of inherited juvenile amyotrophic lateral sclerosis (ALS16). Sig1R localizes to the mitochondria‐associated membrane (MAM), which is an interface of mitochondria and endoplasmic reticulum. However, the role of the MAM in ALS is not fully elucidated. Here, we identified a homozygous p.L95fs mutation of Sig1R as a novel cause of ALS16. ALS‐linked Sig1R variants were unstable and incapable of binding to inositol 1,4,5‐triphosphate receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 63 publications
5
144
1
Order By: Relevance
“…To determine the physical location of MAM within mammalian testes, we then visualized the abundant existence of MAM in germ cells of mouse testes by transmission electron microscope (TEM). Indeed, we found that MAM structure existed in round spermatids (Figure C), which is consistent with the location of MAM in brain tissues . To identify the MAM proteins within testes, we then further solubilized and digested the MAM fractions followed by LC‐MS/MS analyses.…”
Section: Resultssupporting
confidence: 78%
“…To determine the physical location of MAM within mammalian testes, we then visualized the abundant existence of MAM in germ cells of mouse testes by transmission electron microscope (TEM). Indeed, we found that MAM structure existed in round spermatids (Figure C), which is consistent with the location of MAM in brain tissues . To identify the MAM proteins within testes, we then further solubilized and digested the MAM fractions followed by LC‐MS/MS analyses.…”
Section: Resultssupporting
confidence: 78%
“…These data indicate that Kv2.1 clusters are strategically situated at specific somatic synapses in conjunction with other signalling proteins including S1R and NRG1. S1R is a highly dynamic chaperone-like protein present in the SSC, which is involved in ALS when mutated50. S1R may operate here in a similar way to that described for mitochondrion-associated ER membrane in Ca 2+ signalling via IP3 receptors, perhaps in collaboration with M2-receptor cholinergic activation505152.…”
Section: Discussionmentioning
confidence: 67%
“…S1R is a highly dynamic chaperone-like protein present in the SSC, which is involved in ALS when mutated50. S1R may operate here in a similar way to that described for mitochondrion-associated ER membrane in Ca 2+ signalling via IP3 receptors, perhaps in collaboration with M2-receptor cholinergic activation505152. Thus, by modulating spatiotemporal calcium signals, S1Rs may regulate either voltage-gated calcium channels or potassium channels53, both of which have an impact on neuronal excitability through a mechanism that acts via either G-protein-dependent M2 receptor activation or channel phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The chaperoning of IP3R by Sig-1R was shown to protect cells against stress in neurons [134][135][136][137][138] as well as cardiomyocytes [139,140]. Alteration of this mechanism has been linked with neurological disorders such as Huntington's disease [141], amyotrophic lateral sclerosis (ALS) [142,143], and cancer [144,145]. In addition, sustained Sig-1R activation can lead to excessive calcium transfer to mitochondria leading to cell death as it was recently shown in brain endothelial cells [146].…”
Section: Inositol 145-trisphosphate Receptor (Ip3r)mentioning
confidence: 99%
“…Several splice variants and mutations of the S1R were identified leading to the loss of the ability to bind IP3R and sensitizing cell to apoptosis upon ER stress [147]. Among those Sig-1R variants, some have been linked with neurodegenerative disorders such as ALS [142,143]. The Sig-1R is targeted by many drugs that can be used to modulate IP3R calcium signaling.…”
Section: Inositol 145-trisphosphate Receptor (Ip3r)mentioning
confidence: 99%